Integration Questions

Question Number 105386 by bemath last updated on 28/Jul/20

$$\int\:\frac{{x}^{\mathrm{3}} }{\sqrt{\left({a}^{\mathrm{2}} +{x}^{\mathrm{2}} \right)^{\mathrm{3}} }}\:{dx}\: \\$$

Answered by john santu last updated on 28/Jul/20

$${by}\:{substitute}\:{x}\:=\:{a}\:\mathrm{tan}\:\theta \\$$$${I}=\:\int\:\frac{{x}^{\mathrm{3}} {dx}}{\sqrt{\left({a}^{\mathrm{2}} +{x}^{\mathrm{2}} \right)^{\mathrm{3}} }}\:=\:{a}\int\:\frac{\mathrm{tan}\:^{\mathrm{3}} \theta}{\mathrm{sec}\:^{\mathrm{3}} \theta}.\mathrm{sec}^{\mathrm{2}} \theta\:{d}\theta \\$$$${I}=\:{a}\int\:\frac{\mathrm{tan}\:^{\mathrm{3}} \theta}{\mathrm{sec}\:\theta}{d}\theta\:=\:{a}\int\:\frac{\mathrm{sin}\:^{\mathrm{3}} \theta}{\mathrm{cos}\:^{\mathrm{2}} \theta}\:{d}\theta \\$$$${set}\:{w}\:=\:\mathrm{cos}\:\theta \\$$$${I}=\:−{a}\int\:\frac{\mathrm{1}−{w}^{\mathrm{2}} }{{w}^{\mathrm{2}} }\:{dw}={aw}+\frac{{a}}{{w}}+{c} \\$$$$\therefore\:{I}={a}\:\mathrm{cos}\:\theta+\frac{{a}}{\mathrm{cos}\:\theta}+{c} \\$$$${I}=\:\frac{{a}^{\mathrm{2}} }{\sqrt{{a}^{\mathrm{2}} +{x}^{\mathrm{2}} }}\:+\:\sqrt{{a}^{\mathrm{2}} +{x}^{\mathrm{2}} }\:+\:{c}\: \\$$$$\left({JS}\:\spadesuit\blacklozenge\right) \\$$

Answered by mathmax by abdo last updated on 28/Jul/20

$$\mathrm{I}\:=\int\:\:\frac{\mathrm{x}^{\mathrm{3}} }{\sqrt{\left(\mathrm{a}^{\mathrm{2}} \:+\mathrm{x}^{\mathrm{2}} \right)^{\mathrm{3}} }}\mathrm{dx}\:\mathrm{we}\:\mathrm{do}\:\mathrm{the}\:\mathrm{changement}\:\mathrm{x}\:=\mathrm{asht}\:\Rightarrow \\$$$$\mathrm{I}\:=\int\:\frac{\mathrm{a}^{\mathrm{3}} \:\mathrm{sh}^{\mathrm{3}} \mathrm{t}}{\sqrt{\mathrm{a}^{\mathrm{6}} \left(\mathrm{cht}\right)^{\mathrm{6}} }}\:\mathrm{ach}\left(\mathrm{t}\right)\mathrm{dt}\:=\int\:\frac{\mathrm{a}^{\mathrm{3}} \:\mathrm{sh}^{\mathrm{3}} \mathrm{t}}{\mathrm{a}^{\mathrm{3}} \mathrm{ch}^{\mathrm{3}} \mathrm{t}}\:×\mathrm{ach}\left(\mathrm{t}\right)\mathrm{dt} \\$$$$=\mathrm{a}\:\int\:\:\frac{\mathrm{sh}^{\mathrm{3}} \mathrm{t}}{\mathrm{ch}^{\mathrm{2}} \mathrm{t}}\mathrm{dt}\:=\mathrm{a}\:\int\:\:\frac{\mathrm{sh}^{\mathrm{2}} \mathrm{t}\:\mathrm{sht}}{\mathrm{ch}^{\mathrm{2}} \mathrm{t}}\mathrm{dt}\:=\mathrm{a}\:\int\:\frac{\mathrm{sht}\left(\mathrm{ch}^{\mathrm{2}} \mathrm{t}−\mathrm{1}\right)}{\mathrm{ch}^{\mathrm{2}} \mathrm{t}}\mathrm{dt} \\$$$$=\mathrm{a}\:\int\:\mathrm{sh}\left(\mathrm{t}\right)−\mathrm{a}\:\int\:\:\frac{\mathrm{sht}}{\mathrm{ch}^{\mathrm{2}} \mathrm{t}}\mathrm{dt}\:=\mathrm{ach}\left(\mathrm{t}\right)\:+\frac{\mathrm{a}}{\mathrm{ch}\left(\mathrm{t}\right)}\:+\mathrm{c} \\$$$$\mathrm{but}\:\mathrm{t}\:=\mathrm{argsh}\left(\frac{\mathrm{x}}{\mathrm{a}}\right)\:=\mathrm{ln}\left(\frac{\mathrm{x}}{\mathrm{a}}+\sqrt{\mathrm{1}+\frac{\mathrm{x}^{\mathrm{2}} }{\mathrm{a}^{\mathrm{2}} }}\right)\:\mathrm{and}\:\mathrm{ch}\left(\mathrm{t}\right)\:=\sqrt{\mathrm{1}+\mathrm{sh}^{\mathrm{2}} \mathrm{t}} \\$$$$=\sqrt{\mathrm{1}+\frac{\mathrm{x}^{\mathrm{2}} }{\mathrm{a}^{\mathrm{2}} }}\:\Rightarrow\mathrm{I}\:=\mathrm{a}\sqrt{\mathrm{1}+\frac{\mathrm{x}^{\mathrm{2}} }{\mathrm{a}^{\mathrm{2}} }}\:+\frac{\mathrm{a}}{\sqrt{\mathrm{1}+\frac{\mathrm{x}^{\mathrm{2}} }{\mathrm{a}^{\mathrm{2}} }}}\:\:+\mathrm{C} \\$$